2007
DOI: 10.1080/09638280701568627
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injection to facilitate rehabilitation of muscle imbalance syndromes in sports medicine

Abstract: Intramuscular injection of Botulinum toxin to produce reduction of focal muscle overactivity, and localized muscle spasm, has been utilized therapeutically for almost two decades. Muscle overactivity in neurologically normal muscle, where an imbalance exists between a relatively overactive muscle and its less active synergist or antagonist, can inhibit control of the antagonist producing a functional muscle imbalance. This brief review provides an overview of the role of muscle imbalance in sports-related pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The concept of muscle imbalance has been characterized as hypertrophy or high recruitment of one muscle or muscle group as linked to an atrophy response in opposing muscles [ 43 , 44 ]. Muscle imbalance has been implicated in underlying such conditions as lumbopelvic instability, lower back pain, susceptibility to knee injury, and shoulder pathology [ 43 , 45 , 46 ]. Based on observations of patients, phasic muscles (rather than tonic postural muscles) have been considered susceptible to possible atrophy and weakness from muscle imbalance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of muscle imbalance has been characterized as hypertrophy or high recruitment of one muscle or muscle group as linked to an atrophy response in opposing muscles [ 43 , 44 ]. Muscle imbalance has been implicated in underlying such conditions as lumbopelvic instability, lower back pain, susceptibility to knee injury, and shoulder pathology [ 43 , 45 , 46 ]. Based on observations of patients, phasic muscles (rather than tonic postural muscles) have been considered susceptible to possible atrophy and weakness from muscle imbalance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of intervention delivery was by audio, with more than half of the studies using brief audio recordings (n = 49). After this, the most common mode of administration was verbal instructions (n = 14) by instructors or experimenters (Cullen et al 2007;Gamboa et et al 2010b, c). A further 13 studies used interventions used written instructions (Baquedano et al 2017;Herwig et al 2010;Hofmann et al 2009;A.…”
Section: Mode Of Administrationmentioning
confidence: 99%
“…Side effects of btxA injections include allergic reactions and permanent muscle and tendon injury. Although current evidence does not support the use of botulinum toxin injections for tendon injuries, studies have shown that intramuscular injection of btxA can provide short‐term reduction of local muscle overactivity [73‐76]. In one multicenter study [77], 130 subjects with epicondylitis were treated with btxA injections.…”
Section: Pharmacological Treatment Of Regional Muscle Pain and Sportsmentioning
confidence: 99%